2017
DOI: 10.1016/j.coisb.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Global variation in gene expression and the value of diverse sampling

Abstract: The genomics era has accelerated our understanding of how genetic and epigenetic factors influence both normal variable traits and disease risk in humans. However, the majority of “omics” studies have focused on individuals living in urban centers, primarily from Europe and Asia, neglecting much of the genetic and environmental variation that exists across worldwide populations. Comparative studies of gene regulation in ethnically diverse populations are informing our understanding of how evolutionary forces h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Our application of PrediXcan to archaic genomes is a powerful approach for studying the evolution of gene regulation and the biology of archaic groups. The molecular machinery and genetic architecture of gene regulation are largely conserved across humans, and most common human regulatory variants have similar effects across populations 32,33 . Our approach enabled us to study the regulation of many genes by archaic hominin sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Our application of PrediXcan to archaic genomes is a powerful approach for studying the evolution of gene regulation and the biology of archaic groups. The molecular machinery and genetic architecture of gene regulation are largely conserved across humans, and most common human regulatory variants have similar effects across populations 32,33 . Our approach enabled us to study the regulation of many genes by archaic hominin sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The substitution-based approaches, nevertheless, are often at odds with emerging data on the evolutionary history of alleles involved in reproductive isolation (Marques et al, 2019;Satokangas et al, 2020). In addition, many models make an implicit assumption that two allopatric lineages only differ by fixed alleles, which does not capture the empirical diversity among individuals' gene expression (Kelly et al, 2017;Tyler et al, 2017;Gould et al, 2018;Mogil et al, 2018;Ryu et al, 2019) nor the observed importance of regulatory disruption and standing genetic variation in generating reproductive isolation (Hopkins and Rausher, 2011;Wittkopp and Kalay, 2012;Guerrero et al, 2016;Rougeux et al, 2019;Morgan et al, 2020). More importantly, substitutions originating from de-novo mutations fail to explain the recent evidence that alleles underlying reproductive barriers often predate speciation events and can evolve along parallel evolutionary trajectories (Kaeuffer et al, 2012;Sicard et al, 2015;Meier et al, 2017;Nelson and Cresko, 2018;Wang et al, 2019;Duranton et al, 2019;Marques et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…28 Gene regulation is likely to play a critical role for many complex traits as 29 trait-associated variants are enriched in regulatory, not protein-coding, regions [9][10][11][12][13]. 30 Numerous expression quantitative trait loci (eQTLs) studies have provided insight into 31 how genetic variation affects gene expression [14][15][16][17]. While eQTLs can act at a great 32 distance, or in trans, the largest effect sizes are consistently found near the transcription 33 start sites of genes [14][15][16][17].…”
Section: Introduction 17mentioning
confidence: 99%
“…30 Numerous expression quantitative trait loci (eQTLs) studies have provided insight into 31 how genetic variation affects gene expression [14][15][16][17]. While eQTLs can act at a great 32 distance, or in trans, the largest effect sizes are consistently found near the transcription 33 start sites of genes [14][15][16][17]. Because gene expression shows a more sparse genetic Fig 1. Summary of eQTL analyses in MESA populations True positive rate π1 statistics [29] for cis-eQTLs are plotted vs. the number of PEER factors used to adjust for hidden confounders in the expression data of both discovery and replication populations.…”
Section: Introduction 17mentioning
confidence: 99%